Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Keputusan Pembelian Pada Marketplace Lazada - Rafa Naufal Hanifah; Arif Fadila (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the influence of online customer reviews and online customer ratings on purchasing decisions on the Lazada marketplace. In this study using a descriptive verification approach with quantitative methods. The sample used in this study was 400 respondents. Sampling using the Nonprobability Sampling method. The test stages used were validity test, reliability test, classic assumption test, multiple linear regression analysis technique and hypothesis testing using t test, f test and coefficient of determination using SPSS 26 tools. The results of this study were obtained by Online Customer Reviews and Online Customers Ratings have a positive and significant partial effect on purchasing decisions on the Lazada marketplace with variable values of 20.8% and 91.0% respectively. While Online Customer Reviews and Online Customer Ratings simultaneously influence purchasing decisions on the Lazada marketplace, they contribute 39.2% to purchasing decisions, while the remaining 60.8% is contributed by other factors not examined that influence purchasing decisions (Y ).